2016
DOI: 10.1111/chd.12402
|View full text |Cite
|
Sign up to set email alerts
|

Fused cardiac hybrid imaging with coronary computed tomography angiography and positron emission tomography in patients with complex coronary artery anomalies

Abstract: In this case series of middle-aged patients with CCAA, perfusion defects as assessed by semiquantitative PET-MPI were rare and attributable to concomitant CAD rather than to the anomalous vessel itself. By contrast, impaired MBF as assessed by quantitative hybrid CCTA/PET-MPI was revealed in the majority of patients in the vessel territories subtended by the anomalous coronary artery itself. Fused hybrid CCTA/PET-MPI incorporating information on morphology and on semiquantitative and quantitative myocardial pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
(81 reference statements)
0
19
0
1
Order By: Relevance
“…This approach is supported by most authors 1 . A recent small case series by Gräni et al 7 suggested hybrid imaging with coronary computed tomography angiography and positron emission tomography is superior to perfusion imaging alone at detecting impaired myocardial blood flow in patients with complex coronary artery anomalies. The significance of such changes has yet to be assessed prognostically but could potentially aid risk stratification in such patients.…”
Section: Discussionmentioning
confidence: 87%
“…This approach is supported by most authors 1 . A recent small case series by Gräni et al 7 suggested hybrid imaging with coronary computed tomography angiography and positron emission tomography is superior to perfusion imaging alone at detecting impaired myocardial blood flow in patients with complex coronary artery anomalies. The significance of such changes has yet to be assessed prognostically but could potentially aid risk stratification in such patients.…”
Section: Discussionmentioning
confidence: 87%
“…Advising patients to continue sports at a REC level might be a reasonable option in this setting. Therefore, decisions towards patient management should only be made after implementing clinical data, such as sport- and nonsport-related symptoms, previous sports behavior, the anatomic features of ACAOS, age, and noninvasive stress test results [32-34]. This hypothesis has to be evaluated in larger, multicenter registries in order to adapt recommendations/guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies comparing hybrid imaging with either stand-alone or side-by-side interpretation of the datasets have shown that interpretation was changed based on fused images in almost one-third of patients evaluated for suspected obstructive CAD [ 198 201 ]. Additional patient groups in which hybrid imaging has been shown to provide complementary information are those with congenital coronary anomalies [ 202 ] and patients with recurrent chest pain after CABG [ 203 ]. Furthermore, hybrid imaging can identify patients with microvascular dysfunction without obstructive CAD [ 204 ].…”
Section: Perspectives For Pet Mpimentioning
confidence: 99%